Inovasi Flipbook Berbasis Multimodal Untuk Meningkatkan Literasi Dan Diversifikasi Media Pembelajaran Di Sekolah Dasar - Afriani, Winda; Putra, Ikhza Mahendra; Sanulita, Henny (Universitas Tanjungpura, 2024)
The literacy issue in Indonesia reveals a significant deficiency, with a reading index of only 0.001 according to UNESCO and a ranking of 60th out of 61 countries in reading culture, as reported by WMLN 2016. Low literacy rates among children negatively impact their cognitive development and learning abilities. Studies from PISA 2018 and EGRA indicate that many early-grade students struggle to comprehend reading materials, a situation comparable to stunting in health. This research explores multimodal flipbooks as an innovative solution to enhance literacy and diversify learning media in elementary schools. By integrating text, images, audio, and video, these flipbooks offer an interactive and engaging learning experience. A conceptual qualitative method was employed to analyze the needs and potential for developing teaching materials through this innovative concept. The results demonstrate that multimodal flipbooks are effective in improving literacy and diversifying learning media, providing an attractive alternative to overcome the limitations of conventional media in elementary schools.